Skeptisisme digitalisasi pola pembelajaran pasca gelombang covid-19 - Cahyawati, Rina Susi (Fakultas Sastra Universitas Negeri Malang, 2022)
The Covid-19 pandemic has become one of the triggers for the development of digitalization in the world of education. This is because it is seen as a solution to continue to carry out learning activities without face to face directly. However, digitalization skepticism has emerged in the post-Covid-19 learning pattern. If the installment-generating situation is stable and face-to-face learning is fully enforced, will the use of digitalization remain at its original performance or will its usability and interest decrease? Digitalization is predicted to be an option but its use cannot be done intensively when learning is bold. This is because there are weaknesses in learning courage, so there are considerations to be transferred to other things. However, digitalization is not abandoned because there are certain things that can provide benefits such as creating a new formula, namely face-to-face learning collaboration with the involvement of digitalization elements while educating the public to understand digital literacy in order to survive in the 4.0 and 5.0 era.